SOVEREIGN BOND STABILIZATION, RUPIAH VOLATILITY, AND PORTFOLIO INVESTMENT RESILIENCE IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW BASED ON MODERN PORTFOLIO THEORY - Anggun Wida Prawira; Santoso (Program Studi Manajemen Bisnis Syariah, 2026)
This study examines the interrelationship between sovereign bond stabilization, rupiah volatility, and portfolio investment resilience in Indonesia as an emerging financial market. The study is motivated by increasing exchange-rate pressure, fluctuations in government bond yields, global monetary uncertainty, and the need to maintain investor confidence in Indonesia’s capital market. Although previous studies have examined sovereign bond yield dynamics, macroprudential policy, exchange-rate risk, and portfolio optimization separately, limited research has integrated these issues into a unified framework for investment resilience in Indonesia. Using a Systematic Literature Review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework, this study synthesizes 25 selected publications from Crossref, Scopus, and Google Scholar published between 2020 and 2024, supported by recent policy and market developments in 2026. The findings indicate that sovereign bond stability is shaped by macroeconomic fundamentals, fiscal credibility, exchange-rate expectations, liquidity conditions, geopolitical risk, investor structure, and policy coordination. The synthesis further suggests that bond stabilization mechanisms, diversified sovereign financing instruments, and coordinated monetary–fiscal policy can enhance portfolio resilience by reducing yield volatility, strengthening investor confidence, and mitigating capital-flow reversal risks. This study contributes to the literature by developing an integrated conceptual perspective linking sovereign bond-market stability, currency volatility, and portfolio investment resilience in an emerging-market context. The findings provide practical implications for policymakers, institutional investors, and portfolio managers seeking to manage financial-market volatility in Indonesia.